STUDI PERILAKU HARIAN MONYET EKOR PANJANG (Macaca fascicularis) DI KAWASAN HUTAN RESORT RANAMESE, TAMAN WISATA ALAM RUTENG, KABUPATEN MANGGARAI TIMUR, PROVINSI NUSA TENGGARA TIMUR - Marianus Dedi Dahar; Maria M. E. Purnama; Norman P.L.B. Riwu Kaho (Wana Lestari, 2021)
This research is about the Study of the Daily Behavior of the Long Tailed Monkey (Macaca fascicularis) in the Forest Area of ​​the Ranamese Resort, Ruteng Nature Tourism Park, East Manggarai Regency, East Nusa Tenggara Province. The purpose of this study was to determine the daily behavior of long-tailed monkeys in the forest area of ​​Ranamese Resort, Ruteng Nature Tourism Park, East Manggarai Regency, East Nusa Tenggara Province. This research has been carried out during July-September 2020. The study began with collecting the location points of the long-tailed monkeys found using GPS Garmin 64S in three time periods with an interval of 2 hours, namely in period I (at 06.00/08.00 WITA), period II (at 10.00/12.00 WITA). , period III (15.00/17.00 WITA) accompanied by observations of the number of behaviors of long-tailed monkeys (Macaca fascicularis) using the focal animal sampling method. The data obtained were analyzed using non-parametric statistics with the Kruskal Wallis H test. The results showed that the total number of direct encounter points of long-tailed monkeys was 363 points. The highest number of direct encounter points for long-tailed monkeys was in period I (06/08 WITA) with a total of 160 points.The daily behavior frequency of long-tailed monkeys in the Forest Area of ​​Ranamese Resort, Ruteng Nature Tourism Park, East Manggarai Regency, East Nusa Tenggara Province, namely the behavior of moving / moving with a number of 973 (28%) followed by eating behavior 855 (25%), social 706 (21%), agonistic 269 (8%), grooming 251(7%), resting 233 (7%), sexual/mating 134 (4%), nesting 0 (0%). The most dominant behavior of moving/moving while the lowest behavior is making nests. The results of Kruskal Wallis' H test showed that there was a very significant difference between different types of behavior categories (P < 0.05).